A Formação do nutricionista para atuação na Atenção Básica na perspectiva de docentes - Zeminian, Larissa Baungartner (2018)
This qualitative study aims to analyze the nutritionist training in order to work in Primary Health Care from the perspective of lecturers of Higher Public Education Institutions (HPEI) in the southeast of Brazil, through the application of questionnaires containing questions about the participants’ characterization and the students’ training to work in Primary Health Care. The 21 lecturers of 13 HPEI who participated in the study, pointed out the theoretical references used and issues addressed in the teaching of Nutrition, as well as the strategies used in theoretical and practical approaches and traineeships. The results were organized in the following categories: Nutritionist Training in Primary Health Care: theoretical framework, Nutritionist Training in Primary Health Care: from issues addressed to in practice, The training from both theoretical and practical approaches, being discussed in the light of Collective Health, Single Health System of Brazil (SUS – Sistema Único de Saúde), the nutritionist training, the nutritionists’ responsabilities in Collective Health and with the support of the researcher’s own experiences. It is concluded that the theoretical frameworks related to Primary Health Care are strongly approached by the lecturers in their subjects, including those of intersectoral and educational approach, which broadens and qualifies the training; the Primary Health Care consists of a very powerful playing field for having great solving, being an important place of health upgrading and providing a fulfilling job to the professional in the activities with the population, however, its physical structure, professional motivation and resources for nutritional assessment need to be revisited. It is also concluded that public polices of health and nutrition favor the training of the nutritionist to work in Primary Health Care, requiring a more consistent relation, aiming effectiveness in health actions.